2018
DOI: 10.1007/978-1-4939-7724-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining and Computational Modeling of High-Throughput Screening Datasets

Abstract: We are now seeing the benefit of investments made over the last decade in high-throughput screening (HTS) that is resulting in large structure activity datasets entering public and open databases such as ChEMBL and PubChem. The growth of academic HTS screening centers and the increasing move to academia for early stage drug discovery suggests a great need for the informatics tools and methods to mine such data and learn from it. Collaborative Drug Discovery, Inc. (CDD) has developed a number of tools for stori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…On the other hand, the number of HTS datasets has strongly increased in recent years [32,40]. If available for the target of interest, such dataset constitutes an interesting alternative as a test set (containing true instead of assumed inactives, better characterising the chemical diversity of molecules or representing by definition a realistic active-inactive proportion).…”
Section: Selecting a Scoring Function Based On Your Own Evaluationmentioning
confidence: 99%
“…On the other hand, the number of HTS datasets has strongly increased in recent years [32,40]. If available for the target of interest, such dataset constitutes an interesting alternative as a test set (containing true instead of assumed inactives, better characterising the chemical diversity of molecules or representing by definition a realistic active-inactive proportion).…”
Section: Selecting a Scoring Function Based On Your Own Evaluationmentioning
confidence: 99%
“…From a total of seven hits, only one showed a MIC below 10 M and moderate cytotoxicity. Five of the seven M. abscessus hits were either positive in our M. tuberculosis REMA or had been described previously as hits in other M. tuberculosis screening campaigns (16). Upon testing of M. abscessus hits against M. tuberculosis, we identified only one substance (number 2) which seems to possess selective activity against M. abscessus ( Table 1).…”
mentioning
confidence: 74%
“…Hit compound 2, a carbamothioate, and hit compound 3, a thiourea, had MICs of 22 M and 23.7 M, respectively. IC 50 cytotoxicity values were Ͼ100 M. A database search revealed that both substances display known antituberculous activity (Collaborative Drug Discovery Vault) (16). This also holds true for the imidazo-pyridazine compounds 4 to 6, all which displayed an SI of Ͻ1 due to pronounced cytotoxicity.…”
mentioning
confidence: 81%
“…Datasets" that is done by Ekins [18], "Web-based Drug Repurposing Tools" that is written be Sam E and Athri P [19], "DRUG Discovery Using Data Mining" that is provided by Charanpreet Kaur and Shweta Bhardwaj [20], and "Using Genetic Algorithms for Data Mining Optimization in an Educational Web-Based System" that is written by Behrouz Minaei-Bidgoli et al [21]. Some of these papers may provide part of the Data Mining functionalities we present in our work, but none are equipped with a strong backend database as we offer in our work.…”
Section: Other Work Include "Data Mining and Computational Modellingmentioning
confidence: 99%